2020
DOI: 10.1097/md.0000000000019814
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine therapy for deep vein thrombosis in a patient with vascular-type Behçet disease

Abstract: Rationale: Behçet Disease (BD) is a chronic inflammatory vasculitis with thrombogenicity and multisystem involvement. Deep vein thrombosis (DVT) in the lower extremities is the most frequent manifestation of vascular involvement in BD. The causes of thrombosis vary widely and include congenital predisposition and acquired factors, but of all the thrombosis, the cause is rarely BD. Furthermore, there are few reports of treatment for thrombosis in BD.Patient concerns: We herein describe the case of an Asian male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…53 Finally, in cases where the thrombus burden remains refractory to standard antiplatelet and anticoagulant therapies, colchicine has been shown to be associated with thrombus resolution. 66 Our 400-patient randomised Colchicine in Percutaneous Coronary Intervention (Colchicine-PCI) trial demonstrated that when given as a standard loading dose prior to tissue injury (coronary stent placement), colchicine significantly dampened the upregulation of IL-6 and CRP. 67 These effects were observed 22-24 hours after the acute event, providing a rationale to administer colchicine earlier in the disease process to prevent clinical manifestations of cytokine-induced injury.…”
Section: Colchicine In Non-rheumatological Inflammatory Conditionsmentioning
confidence: 99%
“…53 Finally, in cases where the thrombus burden remains refractory to standard antiplatelet and anticoagulant therapies, colchicine has been shown to be associated with thrombus resolution. 66 Our 400-patient randomised Colchicine in Percutaneous Coronary Intervention (Colchicine-PCI) trial demonstrated that when given as a standard loading dose prior to tissue injury (coronary stent placement), colchicine significantly dampened the upregulation of IL-6 and CRP. 67 These effects were observed 22-24 hours after the acute event, providing a rationale to administer colchicine earlier in the disease process to prevent clinical manifestations of cytokine-induced injury.…”
Section: Colchicine In Non-rheumatological Inflammatory Conditionsmentioning
confidence: 99%
“…For that, these conditions should be treated with specific immunosuppressants or immunomodulatory drugs. Colchicine has recently been successfully used to treat a deep vein thrombosis in Behçet disease, having a therapeutic rationale to reduce the inflammatory state at the endothelial level ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, colchicine reduces lung injury in experimental acute respiratory distress syndrome (ARDS) [ 13 ]. Finally, colchicine may be an effective treatment for inflammation-induced thrombosis [ 14 ]. At variance with anti-IL6/IL-6 receptor antagonists, colchicine is widely available on the market, and inexpensive [ 6 ], and it is, therefore, suitable for massive use in countries where biologics are not easily available.…”
Section: Discussionmentioning
confidence: 99%